Effectiveness of vector control methods for the control of cutaneous and visceral leishmaniasis: A meta-review - Montenegro Quiñonez, Carlos Alberto; Runge-Ranzinger, Silvia; Rahman, Kazi Mizanur; Horstick, Olaf (PLOS Neglected Tropical Diseases, 2021)
Elimination of visceral leishmaniasis (VL) in Southeast Asia and global control of cutaneous leishmaniasis (CL) and VL are priorities of the World Health Organization (WHO). But is the existing evidence good enough for public health recommendations? This meta-review summarises the available and new evidence for vector control with the aims of establishing what is known about the value of vector control for the control of CL and VL, establishing gaps in knowledge, and particularly focusing on key recommendations for further scientific work. This meta-review follows the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) criteria, including (1) systematic reviews and meta-analyses (SRs/MAs) for (2) vector control methods and strategies and (3) for the control of CL and/or VL. Nine SRs/MAs were included, with different research questions and inclusion/exclusion criteria. The methods analysed for vector control can be broadly classified into (1) indoor residual spraying (IRS); (2) insecticide-treated nets (ITNs; including insecticide-impregnated bednets); (3) insecticide-treated curtains (ITCs; including insecticide-treated house screening); (4) insecticide-treated bedsheets (ITSs) and insecticide-treated fabrics (ITFs; including insecticide-treated clothing) and (5) durable wall lining (treated with insecticides) and other environmental measures to protect the house; (6) control of the reservoir host; and (7) strengthening vector control operations through health education. The existing SRs/MAs include a large variation of different primary studies, even for the same specific research sub-question. Also, the SRs/MAs are outdated, using available information until earlier than 2018 only. Assessing the quality of the SRs/MAs, there is a considerable degree of variation. It is therefore very difficult to summarise the results of the available SRs/MAs, with contradictory results for both vector indices and—if available—human transmission data. Conclusions of this meta-review are that (1) existing SRs/MAs and their results make policy recommendations for evidence-based vector control difficult; (2) further work is needed to establish efficacy and community effectiveness of key vector control methods with specific SRs and MAs (3) including vector and human transmission parameters; and (4) attempting to conclude with recommendations in different transmission scenarios.